Potensi Keanekaragaman Satwaliar Untuk Pengembangan Ekowisata Di Laboratorium Lapangan Konservasi Sumberdaya Hutan Dan Ekowisata Hutan Pendidikan Unhas - Amran Achmad; Putu Oka Ngakan; Anwar Umar; Asrianny (Jurnal Penelitian Kehutanan Wallacea, 2013)
This study aims to determine the potential of wildlife diversity that can be developed as an ecotourism attraction in the Field Laboratory of Forest Resources Conservation and Ecotourism, Unhas Educational Forest. The data was collected by survey method using the line transect method and concentration point count method. Data were analyzed to determine the ecological indices, ie; Richness Indices, Evenness Indices, and Diversity Indices. The results showed that Field Laboratory of Forest Resources Conservation and Ecotourism, have the wild life of mammals, birds, insects, reptiles and frogs that have the potential to be used in the development of ecotourism. The wildlife to be developed as an ecotourism attraction, are the Sulawesi Black Monkey, Tarsier, Couscous, Sulawesi Civets, Deer and Wild Boar, as well as a variety of birds, reptiles and frogs.